2018
DOI: 10.3390/atmos9020050
|View full text |Cite
|
Sign up to set email alerts
|

Megacity-Induced Mesoclimatic Effects in the Lower Atmosphere: A Modeling Study for Multiple Summers over Moscow, Russia

Abstract: Urbanization leads to distinct meteorological features of urban environments, and one the best-known is the urban heat island (UHI) effect. For megacities, these features become mesoscale phenomena (scale ≥ 10 km) that are amplified by the tropospheric feedbacks, and have substantial implications on human well-being. For the first time, a three-dimensional statistical description of the megacity-induced meteorological effects extending towards the lower troposphere for summer is acquired on a quasi-climatologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 84 publications
(110 reference statements)
3
50
0
3
Order By: Relevance
“…Prior to comparison of the modelling results and MODIS data, it is important to highlight the key results of the model-observation comparison for air temperature and other meteorological parameters, which are presented in details in previous studies (Varentsov et al 2017a(Varentsov et al , 2017b(Varentsov et al , 2018. Such comparison has shown that the model successfully reproduces the summertime meteorological regime of the Moscow region including the temporal variability of mean rural temperature and CLUHI intensity for the city center, including the diurnal and synoptic-scale variations and extremes of CLUHI intensity that reaches 8-9°С at calm and clear nights (Fig.…”
Section: Comparison Of the Modelling Results Remote Sensing And In Smentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to comparison of the modelling results and MODIS data, it is important to highlight the key results of the model-observation comparison for air temperature and other meteorological parameters, which are presented in details in previous studies (Varentsov et al 2017a(Varentsov et al , 2017b(Varentsov et al , 2018. Such comparison has shown that the model successfully reproduces the summertime meteorological regime of the Moscow region including the temporal variability of mean rural temperature and CLUHI intensity for the city center, including the diurnal and synoptic-scale variations and extremes of CLUHI intensity that reaches 8-9°С at calm and clear nights (Fig.…”
Section: Comparison Of the Modelling Results Remote Sensing And In Smentioning
confidence: 99%
“…The mixed-layer height is at least eight to ten times smaller during the night than during the day so that urban heat release is distributed over a significantly smaller depth (Bohnenstengel et al 2011). As a result, the nighttime UHI over a megacity typically extents to the lower troposphere for 100-150 m only (Wouters et al 2013;Varentsov et al 2018). Within the canopy layer the UHI is much more intense at nighttime than at daytime.…”
Section: Discussionmentioning
confidence: 99%
“…The annual mean temperature anomaly (deviation from the mean rural value) is 2 °C for Balchug station and about 1 °C for the park stations MSU and VDHKh [24]. According to the recent detailed studies of Moscow climate features [21,23], the temperature observations at Balchug station are representative of the whole central part of the city, and of some especially densely built areas beyond. Most of the other built areas within the city are typically cooler than the city center, but warmer than the urban parks, and, moreover, rural areas.…”
Section: Methodsmentioning
confidence: 99%
“…Between 1977 and 2016, the average rate of growth of the mean summer temperature (June–August) was 0.6 °C per decade for rural areas [21]. The Moscow megacity forms an intensive urban heat island [22], which manifests itself as a mesoscale temperature anomaly that covers the whole city and even its neighboring regions [21,23]. The urban–rural temperature contrasts could reach up to 13 °C in favorable weather conditions, while the annual mean temperature difference between the city center and rural surroundings is about 2 °C [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…On average, the centre of Moscow megacity is 2 ℃ warmer than surrounding rural areas [27], however, the urban-rural temperature difference could reach up to 14 ℃ [28]. According to the recent observational and modelling studies, the urban-induced temperature anomaly covers the whole city and its nearest suburbs, beyond its administrative limits [29,30]. Moreover, there has been an intensification of the UHI of Moscow, which is caused by urban growth and development and is especially pronounced in summer [27,31].…”
Section: Study Areamentioning
confidence: 99%